Significance of Soft Skills in Educational Process During the Pandemic Caused by the Coronavirus COVID-19 - Pezer, Danijela (Technium Social Sciences Journal, 2021)
Today, an increasing number of jobs require pronounced and developed soft skills, and some kind of digital skills. The coronavirus pandemic COVID-19, only accelerated inevitably, and all stakeholders in the business world had to keep up with many of today’s available technologies and platforms. Although work from home is already known to many companies, in schools and faculties a such way of working is not common, and contact teaching is preferred. The teaching staff are faced with numerous challenges in the new situation, and a new way of knowledge transferring. Based on this fact, in addition to the training of teaching staff, it is necessary to adequately train and prepare students for such a form of teaching, in order to ensure the current level of quality of teaching. Students should be prepared in the best possible way for the challenges that await them in the business world, provide them a quality education in order to easily adapt to the needs of the new digital era required by the labour market. In the knowledge transfer today, except hard and digital skills, soft skills also play a significant role. It is extremely important to raise awareness on this topic, because teamwork, creativity, togetherness and empathy have never been more important and necessary. It is extremely important to show collegiality among employees but also in relation to students and thus also contributing to reduce stress in the teaching pro-cess, especially during the pandemic. Taking all the above into account, through a questionnaire which was conducted at the undergraduate professional study of mechanical engineering, it was tried to gain insight into the importance of soft skills from the students’ perspective. Young educated people are the future of every country, and constant investment in their development and progress is needed.